2015
DOI: 10.1115/1.4029819
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Microencapsulated Phase Change Material Slurry in a Coil Heat Exchanger

Abstract: An experimental study has been carried out to investigate the convective heat transfer and pressure drop characteristics of microencapsulated phase change material (MPCM) slurry in a coil heat exchanger (CHX). The thermal and fluid properties of the MPCM slurries were determined using a differential scanning calorimeter (DSC) and a rotating drum viscometer, respectively. The overall heat transfer coefficient and pressure drop of slurries at 4.6% and 8.7% mass fractions were measured using an instrumented CHX. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The experimental results clearly showed that the viscosity of MPCM slurry is independent of shear rate and the coefficient of variation r X of the viscosity is less than 1.2%. Therefore, it can be concluded that MPCM slurries behaves as Newtonian fluids at the tested mass fractions, ranging from 2.1% to 10.9%, which is consistent with previous experiments and observations [1,3,8,9]. Using the temperature-dependent viscosity data, the Andrade equation was used for estimating fluid viscosity as a function of fluid temperature, which is defined as follows:…”
Section: Viscosity Measurement Of Mpcm Slurrysupporting
confidence: 54%
See 4 more Smart Citations
“…The experimental results clearly showed that the viscosity of MPCM slurry is independent of shear rate and the coefficient of variation r X of the viscosity is less than 1.2%. Therefore, it can be concluded that MPCM slurries behaves as Newtonian fluids at the tested mass fractions, ranging from 2.1% to 10.9%, which is consistent with previous experiments and observations [1,3,8,9]. Using the temperature-dependent viscosity data, the Andrade equation was used for estimating fluid viscosity as a function of fluid temperature, which is defined as follows:…”
Section: Viscosity Measurement Of Mpcm Slurrysupporting
confidence: 54%
“…For similar rheological properties of MPCM slurry, a higher latent heat of fusion of PCM can considerably lead to enhanced heat transfer performance. Relevantly, Kong et al [8] reported that the overall heat transfer coefficient of MPCM slurry, having a latent heat of fusion of 152 J/g, was higher than that of water when using an industrial coil heat exchanger. Fig.…”
Section: Heat Transfer Behavior Of Mpcm Slurriesmentioning
confidence: 96%
See 3 more Smart Citations